Teachers’ Perception on Professional Development Needs of Primary EFL Teachers - Nirwana, Nirwana; Ananda, Anisa Rizky; Narpaduita, Pamastu; Inawati, Iin (PROJECT (Professional Journal of English Education), 2025)
This qualitative study investigates the professional development needs of primary school English as a Foreign Language (EFL) teachers in Yogyakarta, Indonesia. The research aims to explore teachers' perceptions regarding their language proficiency, pedagogical strategies, and subject knowledge needs through semi-structured interviews. Participants included two EFL teachers selected based on their teaching experience. Data were collected via recorded interviews, transcribed, and analyzed using thematic analysis to identify key themes related to teachers' professional development needs. Findings indicate a strong demand among teachers for continuous development in language skills, innovative pedagogical approaches, and deeper subject knowledge. The study underscores the importance of tailored professional development programs that address these needs to enhance teaching effectiveness and student learning outcomes in primary EFL education. The study's discussion highlights the implications for future research on the professional development (PD) needs of primary EFL teachers.